Dragon fire - McMann, Lisa (McMann, Lisa. Unwanteds quests, 2020)
Leaving Dev to face the Revinir alone, Thisbe leads a group to Artime to help Fifer, Aaron, and his allies combat the reckless new head mage, Frieda Stubbs.